Randomized Controlled Lifestyle Intervention (LION) Study for Weight Loss and Maintenance in Adults With Obesity—Design and Methods - Reik, Anna; Holzapfel, Christina (Frontiers in Nutrition, 2020)
Introduction Due to the increasing prevalence of obesity, approaches for a more effective treatment especially in the long-term perspective are needed. However, studies on weight loss and maintenance show heterogeneous results with large inter-individual variations. Therefore, it is of interest to identify factors that contribute to inter-individual differences and predict the success of long-term weight management. Methods and analysis The primary outcome of the Lifestyle Intervention (LION) Study is to evaluate the effect of two diets (low carb vs. low fat) and two digital counseling tools (newsletter vs. mobile application) on weight maintenance 12 months after weight loss. The identification of predictive factors (e.g. genetic, epigenetic, physiological, psychological) for the success of weight loss and maintenance is a secondary outcome. Men and women with a body mass index (BMI) between 30.0 and 39.9 kg/m², aged 18 to 65 years, and without severe diseases are considered eligible. After phenotyping (e.g. anthropometry, resting metabolic rate, meal challenges, blood parameters) participants will follow a formula-based, low-calorie diet for 8 weeks. Subsequently, 252 participants will be randomized into one of the four intervention groups (low carb/app, low carb/newsletter, low fat/app, low fat/newsletter) for the 12-month weight maintenance step. The study will be concluded after another 12 months of follow-up. Results should provide indications for successful weight management and give insights into the personalized treatment of obesity. Trial registration number This study has been registered within clinicaltrials.gov (NCT04023942) and the German Clinical Trials Register (DRKS00017819).